Hospital uncompensated care and patient experience: An instrumental variable approach. (9th January 2019) - Camilleri, Susan; Diebold, Jeffrey
Abstract : Objective: Examine the endogenous relationship between uncompensated care and hospital patient experience scores. Data Sources/Study Setting: The Hospital Consumer Assessment of Healthcare Providers and Systems Survey, CMS Healthcare Cost Report Information System, and the US Census Bureau. Study Design: The exogenous change in uncompensated care caused by the 2014 Medicaid expansion was exploited to measure the effect of uncompensated care on patient experience scores using a 2SLS regression with instrumental variables approach. Data Collection/Extraction Methods: U.S. general, short‐term hospitals whose DSH status remained constant and had nonmissing data for 2011‐2015, which totaled 969 unique hospitals per year. Principal Findings: The effect of uncompensated care on patient experience was in the predicted direction, with three of the 10 measures being statistically significant. A one percentage point increase in uncompensated care costs resulted in a 0.25‐0.50 percentage point decrease in select patient experience scores. Conclusions: Results indicate a weak relationship between uncompensated care and patient experience scores, as a reduction in uncompensated care is related to quality improvement for some hospitals. These findings have implications for hospitals as they navigate changing reimbursement structures and policy makers considering changes to Obama‐era health care reforms.